Polymorphism of Metastasis Suppressor Genes MKK4 and NME1 in Kashmiri Patients with Breast Cancer. Issue 6 (10th August 2016) - Iqbal, Beenish; Masood, Akbar; Lone, Mohd Maqbool; Lone, Abdul Rashid; Dar, Nazir Ahmad
Abstract: Genetic polymorphisms in metastatic suppressor genes like MKK4 and NME1 are not well studied in breast cancer. Hence, we analyzed the relationship between MKK4 and NME1 polymorphisms and breast cancer risk in Kashmir, India. The different genotypes of NME1 and MKK4 genes were analyzed by polymerase chain reaction and restriction fragment length polymorphism in 130 breast cancer cases and 200 age‐ and sex‐matched controls. Conditional logistic regression models were used to assess the association of various genotypes with breast cancer. In this study, we found an inverse association between MKK4 promoter polymorphism and breast cancer risk. As compared to TT (wild) genotype, individuals with TG (heterozygous) (OR = 0.32; 95% CI = (0.17–0.58) and GG (mutant) (OR = 0.13; CI = 0.04–0.40) genotypes showed decreased risk of breast cancer. When participants were classified on the basis of lymph node involvement, a strong association between NME1 heterozygous genotype (OR = 3.82; CI = (1.54–9.44) and breast cancer was found.